KELAYAKAN MEDIA KOMIK SAINS PADA SUBMATERI NUTRISI MAKANAN SMA KELAS XI - Yanuarini, Agustin Nur Intan; Putri Panjaitan, Ruqiah Ganda; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to determine the feasibility of science comics as media of learning in food nutrition submaterial. The form of research used is descriptive. The stages of making science comics is a) determining the title and idea of the story, b) determining the character of the characters and storyline, c) making storyboards, d) drawing in the form of sketches, e) image thickening, f) scanning, layout, and editing, then g) making a synopsis of the story. The instrument used in this study was validation sheet. The feasibility of science comics was measured thought test validity by 6 validators, consist of 3 media expert validators and 3 material expert validators. Validity test of media experts used 3 aspects of format, content, and language. Validity test of material experts used 6 aspects of integration, emphasis, balance, form, design and color, images and writing. The results of validation analysis of science comic on sub material food nutrition is considered feasible to be used as a media of learning with the average validation of material experts is 3,12 and validation of media expertsÂ  is 3,65.Keywords: Science Comics, Media, Sub Material Food Nutrition Â